Common Errors in Word order among Uzbek Learners of English a Contrastive Perspective - G‘ulomova , Sevinchxon Muxiddinovna; Satibaldiyeva , Nigora Alimqulovna (The Lingua Spectrum, 2026)
The article focuses on examining common word order mistakes made by Uzbek learners of English based on contrastive analysis. The importance of learning word order is that it directly affects grammatically correct and clear communication in a foreign language. English and Uzbek languages belong to different language families and sentence structure is a main component of all sentences. As a result, students have difficulties in using syntactic structures correctly when composing sentences in English. Both languages have different syntactic structures and this difference leads to errors in language learners. It is widely acknowledged that Uzbek language mainly follows SOV (Subject-object-verb) word order, and the English language is SVO (Subject-verb-object) structure. This structural difference is one of the main reasons for negative transfer in second language acquisition. This main difference causes learners to transfer native patterns from native language into English. The study analyzes their typical errors, explains their causes and suggests pedagogical strategies to reduce the errors encountered in language learning. The results of the research serve to improve the teaching methodology and increase students’ understanding of the syntactic differences between the two languages.